Dynamic attention-based view of corporate headquarters in MNCs - Tomi Laamanen (Journal of Organization Design, 2019)
While the usefulness of the attention-based view in understanding the role of headquarters-subsidiary relationships in multinational companies (MNC) is well established, recent research on corporate headquarters (CHQ) has moved beyond the simplistic conception of CHQ as a unitary entity. In this point of view, I review the development of the attention-based view and its use in research on CHQs in MNCs. Developing a better understanding of the dynamics of attention between the different subsidiaries and the increasingly dispersed and disaggregated headquarters activities in MNCs requires a more dynamic view of attention. Building on the recently introduced dynamic attention-based view, I identify potential research areas emerging from the application of the dynamic attention-based view to research on CHQ activities in MNCs.
Keywords: 650